Penyuluhan Masyarakat Melalui Peningkatan Ekonomi Desa Berkelanjutan Berbasis Komoditas Lokal Desa Pasiran, Kecamatan Bantan, Kabupaten Bengkalis - Indra Suandy; Budijono Budijono; Endang Purnawati Rahayu; Riza Fitriana (CANANG: Jurnal Pengabdian Masyarakat, 2025)
Sustainable village economic development is an important strategy for improving the welfare of rural communities in Indonesia. This community service aims to enhance community understanding of local commodity potential for developing village economy. This service identifies and optimizes local commodity potential in Pasiran Village, Bantan District, Bengkalis Regency.The method used is community discussions as the main approach. This activity is carried out to increase community knowledge and understanding of village economy based on local commodities. The empowerment program empowers communities in improving and managing natural resources that have the potential to develop community economy.The results of the community service show that the community understands superior local commodities, marketing strategies, as well as the development of small and medium enterprises, Village-Owned Enterprises (BUMDes), and red and white cooperatives that are managed jointly. This program successfully identified superior local commodities in the region. The research concludes that local commodities with technology support and community empowerment can be an effective solution to improve village economy sustainably